External illumination photonic therapies for pneumonia: experimental models and light propagation simulation - Tovar, Johan Sebastian Diaz (2024)
Lower respiratory infections, pneumonia, remains a significant global health challenge, exacerbated by rising antimicrobial resistance, which limits the effectiveness of traditional antibiotic treatments. Antimicrobial photodynamic therapy (aPDT) offers a promising alternative, using light to activate photosensitizers that generate reactive oxygen species, killing microbial cells. This study explores the use of 808 nm wavelength light to penetrate the thoracic wall and activate indocyanine green (ICG) for a photodynamic response in the lungs. A custommade laser panel, emitting light at an irradiance of 78 ± 10 mW/cm2 and centered at 808 nm, was developed for this purpose. Monte Carlo simulations were performed to model photon migration through thoracic wall tissues, identifying the skin and subcutaneous fat as the primary absorbers. In ex vivo experiments using a pig thoracic cage, 3% to 5% of the emitted irradiance were transmitted through the thoracic wall. Despite this low transmission, a 99.9% reduction of Streptococcus pneumoniae was achieved after 42.6 minutes of irradiation, demonstrating the potential efficacy of aPDT. In vivo experiments on a 34 kg pig further supported these findings, with 15% of the emitted irradiance reaching the lung tissue. These results suggest that external thoracic illumination with NIR light can achieve therapeutic fluence levels necessary for lung photobiomodulation and photodynamic inactivation. Complementary Monte Carlo simulations using 3D anatomical models derived from human CT scans evaluated light dosimetry across different lung conditions, including pneumonia and COVID-19. These simulations revealed significant variations in energy deposition and fluence distribution within lung lobes under different pathological conditions and light source configurations. In summary, this study highlights the potential of external NIR light to effectively penetrate the thoracic wall and achieve photodynamic inactivation within the lungs. The combination of experimental data and detailed anatomical modeling is crucial for optimizing light-based therapies for respiratory diseases.